Improving the indicators of schoolchildren's adaptation to physical activity using an individual approach, taking into account the types of vegetative regulation - V. V. Gorelik; S. N. Filippova; N. N. Nazarenko (National Electronic Information Consortium (NEICON), 2023)
Purpose: physiological substantiation of the physical activity selection based on the differences in the functional state of schoolchildren with different types of cardiovascular system autonomic regulation.Methods: 60 schoolchildren, 12 years old, were examined. The experimental group consisted of schoolchildren who were engaged in physical exercises for 6 months according to the developed individual typological program. Students in the control group followed the school programm. The assessment of the functional state was carried out by the method of "Express assessment of the physical health of schoolchildren" and the method of diagnosing indicators of heart rate variability.Results: at the beginning of the survey, the indicators in the experimental group and the control group were determined by the characteristics of 4 types of autonomic regulation: I, II, III, IV. Of these, I, II corresponded to the predominance of sympathetic-tonic destabilizing influences on the cardiovascular system, in IV parasympathetic influences prevailed, manifested in the asthenia of the functional state of students. Whereas type III refers to the physiological norm and manifested itself in the form of a balance of regulatory influences of the parts of the autonomic nervous system.Conclusions: at the control examination, the indicators of adaptation and health improved in all types of schoolchildren, while in the control group there was no positive dynamics of indicators of adaptation and health. This testifies to the effectiveness of individually typologically oriented classes at a physical education lesson as having a health-improving effect on schoolchildren.